Prioritizing Sediment Generation Potential of Sub-Watersheds Using the Best-Worst Method and Observed Sediment Data - Ali Nasiri Khiavi; Seyed Hamidreza Sadeghi; Michael Maerker; Azadeh Katebikord; Padideh Sadat Sadeghi; Seyed Saeid Ghiasi; Mehdi Vafakhah (تحقیقات منابع آب ایران, 2025)
This study investigated the zoning of Sub-Watersheds (SWs) in Taleqan Watershed in Alborz Province regarding Sediment Generation Potential (SGP) using the Multi-Criteria Decision-Making (MCDM)-based Best-Worst Method (BWM). The BWM approach was employed to prioritize the SWs. To this end, Principal Component Analysis (PCA) assisted in identifying the criteria conditioning SGP and after quantifying these criteria, a decision network was created considering their impacts. Subsequently, SGP was classified into five different categories using ArcGIS 10.8 software. The MCDM method was validated using observed sediment data from 18-gauge stations in the outlet of SWs. The results indicated that SW6 was identified as a critical area from the viewpoint of SGP, with northern SWs generally demonstrating a higher potential for sediment generation than southern SWs. The prioritization of SWs revealed that the BWM approach had 33.33% number-wise similarity with that obtained based on observed data. Notably, the percentage of similarity between the BWM approach and observed data in SGP classification was approximately 50% in the low and very low categories. The independent samples t-test showed that the MCDM approach had insignificant differences with the observed data in prioritizing SGP. Moreover, the BWM approach displayed a high correlation with criteria such as time of concentration and bifurcation ratio with respective correlation values of 0.81 and 0.70. The findings underscored the significance of employing various MCDM approaches while considering observed data in sediment yield-related analyses. Thus, a comprehensive and integrated approach at the SW scale is emphasized to enhance sediment management and water resource management.